The effect of refrigerant filling pressure on split AC performance with variations in refrigerant R22, R134A, and R290 - Agung Nugroho; Alfianto; Tabah Priangkoso (JTTM : Jurnal Terapan Teknik Mesin, 2024)
R-22 refrigerant has been recognized as a major cause of climate change and ozone layer depletion, leading to increased interest in finding more environmentally friendly alternatives. Two alternatives being considered are R-134a and R-290. The main objective of this research is to compare the Coefficient of Performance (CoP) performance of split ACs using three types of refrigerants, namely R-22, R-134a, and R-290, taking into account the environmental impact and operational efficiency. The research method involved retrofitting a 1 PK split AC which initially used R-22 with three different types of refrigerant as an experiment. The research process includes test equipment design, equipment installation, and feasibility testing before carrying out experimental testing. Tests were carried out with variations in refrigerant charging pressure of 70 psi, 75 psi, 80 psi, 85 psi, and 90 psi. The research results showed that the largest COP was found in the R-290 refrigerant, reaching a value of 0.86 at a filling pressure of 90 Psi. The largest COP value for R-22 was also found at a filling pressure of 90 psi, namely 0.66. Meanwhile, R-134a achieved the highest COP value at a filling pressure of 90 psi, with a value of 0.57 at a variation of refrigerant filling pressure of 90 Psi. In conclusion, this study provides better insight into the efficiency and environmental impact of the three types of refrigerants discussed. It also provides a useful information basis for the selection of suitable refrigerants in split air conditioning systems, with the aim of environmental conservation and achieving optimal performance